CAN MANAGERIAL SKILLS MITIGATE REAL ACTIVITY MANIPULATION? (EMPIRICAL STUDY ON MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE 2010-2015) - Ronald Tehupiring (Berkala Akuntansi dan Keuangan Indonesia, 2017)
The company's goal to achieve the desired profit target can not only be done through profit manipulation. However, it can also be influenced by managerial skills. A skilled manager will be able to design business processes well by minimizing inputs to achieve optimal output. The purpose of this study is to test whether managerial skills are able to mitigate the manipulation of real activities in manufacturing companies listed on the IDX for the period 2008-2015 obtained through purposive sampling. The results showed that managerial skills were able to mitigate the manipulation of real activities obtained through statistical testing using multiple linear regression.